TUJUH AKHLAK MUSLIM SUKSES DUNIA DAN AKHIRAT TADABBUR SURAT AL-FATIHAH - Syarifuddin (STAI DI AL-HIKMAH, 2024)
One of the greatness and perfection of Islamic law is that it bases its sources and laws on two important sources, namely the Qur'an and the Sunnah of the Prophet Muhammad SAW, who said in the noble hadith (Indeed I have been given the Qur'an and the like thereof), as well as everything we receive in the form of sayings, practices, characteristics, and messages of the Messenger of Allah SAW. Allah SWT, including the Noble Hadith of the Prophet. This valuable prophetic heritage that we receive is a source of Islamic law and guidance. One of the most reliable things in dividing the hadiths into several types is by relying on the chain of transmission and its text, namely the chain of narrators who convey the noble hadiths to us based on the extent of their piety, faith, closeness to them. The Messenger of Allah Shallallahu Alaihi Wasallam and giving him peace, and the extent of their obedience to him. Among the types of hadith are the following: authentic hadith, authentic hadith of other people, weak hadith, and authentic hadith. Through this research, the researcher will clarify all of these things in a simple way until the differences between each become clear.